AN OPEN CONTRACTING FRAMEWORK FOR PUBLIC SECTOR PROCUREMENT: A SEM METHODOLOGY - Naidoo, lawson; Naidoo, Vinessa; Edoun, Emmanuel (Archives of Business Research, 2020)
AN OPEN CONTRACTING FRAMEWORK FOR PUBLIC SECTOR PROCUREMENT: A SEM METHODOLOGY ABSTRACT The main purpose of this study was the development of a framework to implement Open Contracting in South African public sector procurement. The specific objective of this paper is to determine the relationship between the principles of Open Contracting and the pillars for Open Contracting. This was deemed important to provide some insight to the possible components of the recommended framework for the implementation of Open Contracting in public sector procurement. This study followed a quantitative approach. A questionnaire via an online survey was employed to collect the data from a convenience sample of 377 procurement practitioners employed in the South African public sector. Pearson chi-square test (ɑ = 0.05) was used to test for association between any pair of categorical variables. Cronbach’s alpha was applied to test for internal consistency reliability. Structural equation modelling (SEM) was used to test the measurement and structural models and simultaneously examine a series of interrelated dependence relationships among the measured variables. SEM was also used to test the hypotheses in this study. The structural model also indicated a good model fit through the various indices. Therefore, it can be concluded that there is a relationship between Open Contracting principles and pillars for Open Contracting. The findings relating to the research questions, therefore, provided sufficient information to design an Open Contracting Framework to facilitate the implementation of Open Contracting in public sector procurement.